Muon-fluorine entanglement in fluoropolymers - Lancaster, T; Pratt, F; Blundell, S; McKenzie, I; Assender, H (2009)
We present the results of muon spin relaxation measurements on the fluoropolymers polytetrafluoroethylene (PTFE), poly(vinylidene fluoride) (PVDF) and poly(vinyl fluoride) (PVF). Entanglement between the muon spin and the spins of the fluorine nuclei in the polymers allows us to identify the different muon stopping states that occur in each of these materials and provides a method of probing the local environment of the muon and the dynamics of the polymer chains. © 2009 IOP Publishing Ltd.